HER2 Positive Gastric Carcinomas and Their Clinico-Pathological Characteristics - Ognjenovic, Ljubomir; Trajkovski, Gjorgji; Gjoshev, Stojan; Darko DJambaz; Hadzi-Manchev, Dragan; Aleksandar Shumkovski; Volcevski, Goce; Fildishevski, Igor; Nikolova, Dafina; Gordana Petrushevska; Vesna Janevska; Vlado Janevski (ID Design 2012/DOOEL Skopje, 2018)
HER2 protein expression in gastric carcinoma, in correlation with existing, acknowledged prognostic factors which include the parameters that determine the TNM stage of the disease, could become the basis for ongoing research in the field of molecular targeted and personalised therapy.